Kedudukan BPSK dalam Menjamin Prinsip Access To Justice Bagi Konsumen - Ni Luh Novi Astawati; Mochamad Cholil (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
The Consumer Dispute Resolution Agency (BPSK) is a new institution established by the government as a fast and cost-effective solution to consumer disputes. However, its position in the Indonesian judicial system and its effectiveness in ensuring access to justice require review. This research will analyze: (1) the legal position of BPSK, and (2) the extent to which BPSK meets the principle of access to justice for consumers. To know the legal position of BPSK in the Indonesian judicial system and how BPSK contributes to ensuring access to justice for consumers in handling disputes with business actors. The type of research used by the author is legal research with two approaches, namely: (1) statute approach, (2) conceptual approach. Using sources of secondary legal materials obtained indirectly through intermediary media by combining primary and secondary legal materials. The collection techniques applied are bibliography study, and data analysis using prescriptive methods. The results of this research related to BPSK's position in the Indonesian judicial system are outside the judiciary or judicial because BPSK's decision is final and binding, but does not have executive power. The existence of BPSK has played an important role in overcoming the imbalance of legal positions between consumers and business actors, by applying three basic principles, namely accessibility, fairness, and overall effectiveness, which have fulfilled the principle of access to justice. However, the implementation is still facing various challenges of BPSK's unevenness in each region II of the city/district, and low consumer awareness.